Malaspina Printmakers : 14th Annual Members Show. - Emily Carr College of Art, Granville Island, Vancouver (Vancouver : Charles H. Scott Gallery, 1989)
Frioud, Jackie ; Mahon, Patrick L. ; Grafton, Frances ; Carter, Geoff ; Bonnemaison, Michel ; Nelson, Steven G. ; Yager, Robbin ; Eckert, Ron ; Zeigler Sungur, Barbara ; Medsen, Glenn Olav ; Laushway, Lynda ; Biden, Doug ; Smith, Joan
Malaspina Printmakers : 14th Annual Members Show, Charles H. Scott Gallery, Vancouver, Emily Carr College of Art and Design, June 1 - July 16, 1989
English
kunstcatalogus